Impacts of early postpartum behavioral patterns on the fertility and milk production of tropical dairy cows - Aqeel Raza; Kumail Abbas; Theerawat Swangchan-Uthai; Henk Hogeveen; Chaidate Inchaisri (Veterinary World)
Background and Aim: Early postpartum behavioral patterns are pivotal indicators of dairy cow health, reproductive success, and lactation performance, particularly under the environmental stressors of tropical climates. This study aimed to investigate how these behavioral patterns, as captured by smart biosensor data, influence reproductive outcomes, and milk yield in Holstein Friesian cows, with specific emphasis on parity differences and behavioral clustering.